Performance of pistia stratiotes, salvinia molesta, and echhornia crassipes aquatic plants in the tertiary treatment of domestic wastewater with varying retention times - Mustafa H.M.; Hayder G. (MDPI AG, 2023)
Organic matter, nutrients, and chemicals are some of the waste materials found in most domestic wastewaters. The purpose of this research was to evaluate the potentials of Pistia stratiotes, Salvinia molesta, and Eichhornia crassipes aquatic weed plants in the tertiary treatment of secondary domestic wastewater using hydroponic systems. Physicochemical analysis that considered turbidity, phosphate, ammoniacal nitrogen, and nitrate was conducted on the wastewater samples at different retention times of 6, 12, and 24 h for 14 days. The best performance was observed for a 24 h retention treatment system, with up to 91% (P. stratiotes), 94% (S. molesta), and 89.3% (E. crassipes) reduction for turbidity; 81.2% (P. stratiotes), 82.7% (S. molesta), and 88.5% (E. crassipes) for phosphate reduction; 88.66% (P. stratiotes), 90.47% (S. molesta), and 89.11% (E. crassipes) for ammoniacal nitrogen reduction; 83.6% (P. stratiotes), 92.1% (S. molesta) and 93% (E. crassipes) for nitrate reduction. Hence, the application of hydroponic systems in cultivation of the macrophytes proved to be effective in the phytoremediation process by removing the residual nutrients present in the treated secondary domestic wastewater. Additionally, this method can be used for the cultivation of plant-based biomass and other non-edible useful crops using the free nutrients content of the wastewater before its discharge into the natural environment. 2020 by the authors. Licensee MDPI, Basel, Switzerland.